Spectral and Electrochemical Studies on Some Co(II), Ni(II) and Cu(II) Macrocyclic Complexes - Rai, H.C.; Singh, R.K.; Kumar, A.; Kumari, Veena (Asian Journal of Chemistry, 2010)
An interesting group of 34-and 36-membered macrocyclic trinuclear copper(II) and binuclear nickel(II)/cobalt(II) complexes have been isolated by synergic template condensation of bis-(malonodihydrazide) metal(II) complexes with metal (II) complexes of 1,4-bis(2´-formylphenyl)-1,4-dioxabutane or 1,5-bis(2-formylphenyl)- 1,5-dioxapentane in molar ratio 1 : 2 in aqueous ethanolic medium in the presence of sodium acetate. The complexes were obtained in fine crystalline state. Spectral analysis corroborates the macrocyclic structure for the complexes.